The Profile of Bacterial Vaginosis in Academic Hospital Surabaya: A Retrospective Study - Amanda Gracia Manuputty; Sunarko Matodiharjo (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Bacterial vaginosis (BV) is a lower genital tract infection, which occur as a result of vaginal microbiome dysbiosis. This vaginal infection can lead to symptoms such as vaginal discharge, malodor and irritation. It is the most common condition occurred in reproductive age but may give 50–75% of asymptomatic signs. Purpose: To overview new BV patients at the Sexually Transmitted Infection Division of Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya in 2015–2017. Methods: A retrospective study was performed by evaluating medical records of new BV patients, including identity, history taking, examination, diagnosis, treatment, follow up and counselling. Result: The number of new BV cases was 35 (1,38%). The most infected age group was 25–44 years old (51%), and 65.7% of them were married. The most common chief complaint was vaginal discharge without subjective complaints (74.3%), the most common type of complaint was recurrence (48.6%), the most partner roles which affected by BV patients were husbands (51.4%), history of vaginal douching (34.2%), and the most vaginal discharges were severe (75.8%). The whiff test showed positive results and pH > 4.5 in 48.6% of patients. All microscopical preparations showed clue cells. The most prescribed drug was metronidazole. Conclusion: The overview new BV cases showed a small incidence with commonly occurred among women in childbearing age and were asymptomatic. A routine high vaginal swab helps the proper diagnosis and management to prevent the recurrence and complication of BV.